AuditChain: A Trading Audit Platform Over Blockchain - Vishnia, Guy R.; Peters, Gareth W. (Frontiers in Blockchain, 2020)
A blockchain architecture and solution is proposed to audit processing under exchange regulation for trading activity of exchanges. A particular focus is made on dark pools and periodic auctions. An architecture of the solution is described conceptually and an implementation of the proposed solution is made in .NET framework in C# via a RESTful API for chain interaction with the periodic auction venue. The framework proof of concept is tested for different efficiency and latency considerations. This opens the concept to significantly more detailed and extensive developments.